A Vitreous Cyst in an Elderly: A Rare Case Report - Khatri, Anadi; Banstola, Amrit; Karki, Pratap (Birat Journal of Health Sciences, 2019)
This condition has been seen to occur in younger patients. We report here a case of a 54-year - old woman with vitreous cyst.